Institutions and mechanisms for internal conflict resolution: legal and non-legal means in resolving dispute and attaining justice in Malaysia - Mokhtar, Khairil Azmin (Faculty of Law, Universitas Muhammadiyah Yogyakarta, 2016)
Among the questions that the research seek to tackle is should the court become the only saviour of justice? In this article it is argued that the task to combat injustices, produce a just ordering of society, ensure a fair distribution of material and legal resources, safeguard the rule of law, promote equality, ensure proportionality in punishment, and protect entitlements and legitimate expectations should not be put on the shoulders of judges and courts only. It must be spread out and shared by other institutions and by whatever means available. This article seeks to establish that in spite of the crucial role of the court in establishing justice, there are other institutions and mechanisms that can and have been used to achieve justice. In this study Malaysia is used as an example. This article is the result of a qualitative study which employs legal analysis of the constitution and laws in the country. Despite the judiciary’s fundamental role in dispensing justice it have weaknesses and limitations. As shown in this article apart from the formal courts and judges there many institutions and mechanisms which are outside the formal structure of the judiciary that play significant role in resolving dispute, avoiding conflict and realizing justice. As can be observed in this study the role of these institutions becomes more crucial and important especially when the integrity and credibility of the court or judges are questioned and doubted by the public.